2021
DOI: 10.1038/s41467-021-20909-x
|View full text |Cite
|
Sign up to set email alerts
|

Cas9-AAV6 gene correction of beta-globin in autologous HSCs improves sickle cell disease erythropoiesis in mice

Abstract: CRISPR/Cas9-mediated beta-globin (HBB) gene correction of sickle cell disease (SCD) patient-derived hematopoietic stem cells (HSCs) in combination with autologous transplantation represents a recent paradigm in gene therapy. Although several Cas9-based HBB-correction approaches have been proposed, functional correction of in vivo erythropoiesis has not been investigated previously. Here, we use a humanized globin-cluster SCD mouse model to study Cas9-AAV6-mediated HBB-correction in functional HSCs within the c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 47 publications
0
67
0
Order By: Relevance
“…In this context, AAVs can remain episomal, however some studies have also shown vector integration through both non-homologous sites and homologous recombination [34]. Overall, these vectors can achieve long-term expression and are being combined with CRISPR (AAV-based CRISPR systems) to study potential treatments for β-hemoglobinopathies like sickle cell disease (ex vivo gene therapy) [35]. Another additional concern is the size of the gene that we aim to deliver.…”
Section: In Vivo Gene Therapy and Aav Vectorsmentioning
confidence: 99%
“…In this context, AAVs can remain episomal, however some studies have also shown vector integration through both non-homologous sites and homologous recombination [34]. Overall, these vectors can achieve long-term expression and are being combined with CRISPR (AAV-based CRISPR systems) to study potential treatments for β-hemoglobinopathies like sickle cell disease (ex vivo gene therapy) [35]. Another additional concern is the size of the gene that we aim to deliver.…”
Section: In Vivo Gene Therapy and Aav Vectorsmentioning
confidence: 99%
“…For instance, as the absence of IL2RG is lethal for developing lymphocytes, the strong selective advantage of functional T cell progenitors over affected ones may compensate for relatively low editing efficiencies, and <10% of functional HSPCs are predicted to be sufficient to rescue the SCID-X1 phenotype (Schiroli et al, 2017 ). Conversely, the minimal proportion of edited cells must be substantially higher to fully rescue the pathological features of patients affected by other blood disorders, such as hemoglobinopathies or Hyper-IgM1 (Abraham et al, 2017 ; Marktel et al, 2019 ; Vavassori et al, 2021 ; Wilkinson et al, 2021 ). Indeed, suboptimal HDR editing efficiency remains a major constrain for broader application of this technology, as opposed to the high efficiency of NHEJ-mediated editing (Humbert et al, 2019 ; Frangoul et al, 2021 ).…”
Section: Challenges and Advances Toward Clinical Application Of Hspc Gene Editingmentioning
confidence: 99%
“…To resolve the impact of genetic differences between individual on disease modeling, genome editing technology such as the CRISPR/Cas9 system could be used to create disease mutation or deletion in UiPSCs and the healthy control UiPSCs originated from the same individual, enabling us to reveal the disease mechanism caused by a specific genetic defect [ 118 , 119 ]. A recent study using CRISPR/Cas9-mediated beta-globin gene correlation of sickle cell disease patient-derived hematopoietic stem cells in combination with autologous transplantation underlies its potential application in generating gene-correlated autologous UiPSCs-derived cell type for the treatment of genetic diseases [ 120 ]. Thirdly, it has been reported that iPSCs from different somatic origins harbor different patterns of epigenetic signatures, which bias their differentiation potency to specific lineages related to the donor cell while antagonizing other cell fates.…”
Section: Current Challenges and Future Perspectivesmentioning
confidence: 99%